+0  
 
0
37
2
avatar

Simplify \(\dfrac{\frac{x}{x - 1} - \frac{x}{x + 1}}{\frac{x}{x^2 - 1}}\)

 Jun 14, 2020
 #1
avatar+297 
0

Let's first combine the top two fractions in the numerator.

\(\frac{x(x+1)-x(x-1)}{x^2-1}=\frac{x^2+x-x^2+x}{x^2-1}=\frac{2x}{x^2-1}\)

This is what our fraction looks like now:
\(\frac{\frac{2x}{x^2-1}}{\frac{x}{x^2-1}}\)

We can multiply top and bottom by \(x^2-1\), which cancels to \(\frac{2x}{x}=2\)

.
 Jun 14, 2020
edited by thelizzybeth  Jun 15, 2020
 #2
avatar+8286 
0

Multiplying both the numerator and the denominator by \((x^2 - 1)\), we have

 

\(\dfrac{\dfrac{x}{x - 1} - \dfrac{x}{x + 1}}{\dfrac{x}{x^2 - 1}} = \dfrac{x(x + 1) - x(x - 1)}{x} = \dfrac{x((x + 1) - (x - 1))}{x} = \dfrac{2x}{x} = 2\)

This holds for \(x \neq 0 \)

.
 Jun 14, 2020

9 Online Users